Computing systems and the network as a control education arena. Issue 29 (2015) - Leva, Alberto
Abstract: Computers and the network are widely used and studied as a means to provide control education. However, they also offer a wide variety of problems to teach control. This paper concentrates on the second aspect, presenting some didactic activities that are interesting for both control and computer science/engineering students. After motivating the proposed pedagogy from a cultural point of view, also as a means to foster the necessary convergence of the two mentioned communities, some examples of activities are presented and discussed. The purpose is twofold. On one hand, the reader can see how many concepts – ranging from control structures through cyber-physical systems to process/control co-design and more – can be exemplified and experimented with, both in simulation and on real systems that virtually any student already possesses. On the other hand, and maybe most important, the usefulness of those concepts for the design – not just the control – of computing systems, can be appreciated, and constitutes a very promising research and engineering field. To this end, a brief sketch of future perspectives concludes the paper.